Salivary IL-17 and IL-10 as Potential Diagnostic Biomarkers of Different Stages of Periodontitis in Smoker and Nonsmoker Patients - Mohammed, Maha Abdulsalam; Abbas, Raghad Fadhil; Akram, Hadeel Mazin (European Journal of Dentistry, 2023)
Objectives The gold standard in the field of periodontal research currently is to find a valid biomarker that can reliably be used for diagnosing periodontal diseases. Given the limitations of the current diagnostic tools that stall to predict susceptible individuals and determine whether active tissue destruction is occurring, there is an increased urge to develop alternative diagnostic techniques that would compensate for the problems inherited in these available methods, such as measuring levels of biomarkers present in oral fluids such as saliva; so the aim of this study was to determine the diagnostic potential of interleukin-17 (IL-17) and IL-10 to differentiate periodontal health from smoker and nonsmoker periodontitis, and to differentiate among different stages (severities) of periodontitis.Materials and Methods An observational case–control study was performed on 175 systemically healthy participants grouped into healthy as controls and periodontitis as cases. Periodontitis cases were divided according to the severity into stages I, II, and III, and each of the stages was further subdivided into smokers and nonsmokers patients. Unstimulated saliva samples were collected, clinical parameters were recorded, and salivary levels were assayed using enzyme-linked immunosorbent assay.Results Elevated levels of IL-17 and IL-10 were associated with stage I and II compared with the healthy controls. However, a significant decrease in stage III was observed compared with the control group for both biomarkers.Conclusion Salivary IL-17 and IL-10 might be useful for distinguishing periodontal health from periodontitis; however, further research is needed to substantiate their use as potential biomarkers for the diagnosis of periodontitis
Keywords: IL-10; IL-17; periodontitis; diagnosis